APLIKASI COOPERATIF LEARNING JIGSAW DALAM MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR STATISTIKA DASAR MAHASISWA UT MASA REGISTRASI 2009.1 TAHAP II POKJAR BOJONEGORO - Barokah Widuroyekti, (Jurnal Penelitian Pendidikan Matematika dan Sains, 2010)
The classroom action research (CAR) has been done to overcome the low activity of the Open University student learning outcomes on the registration phase II 2009.1 Pokjar Bojonegoro on Basic Statistics course. This research has been done by applying the Jigsaw cooperative learning type. CAR performed consisted of pre-cycles for initial data capture, cycle 1 for the repair stage 1 and cycle 2 for phase 2 improvements. Data obtained through observation sheet and test evaluation results of basic statistical learning materials as well as a questionnaire response to ongoing learning. Data processing techniques with descriptive statistics of average and percentage. The results showed that the application of learning cooperatif Jigsaw Basic Statistics in learning activities can increase the activity of students, from 66.7% of students are active to 93.3%. Increased learning outcomes of the Open University student through the implementation of cooperative learning Jigsaw in Basic Statistics learning activities increased 93.3, namely from 3.3% before being implemented improvement to 96.6% after cycle II.